Perbezaan tanggungjawab peribadi pelajar di Kolej Universiti Islam Melaka (KUIM) / Siti Marhamah Kamarul Arifain … [et al.] - Kamarul Arifain, Siti Marhamah (2015)
Islam is a religion that is practical and appropriate in any situation. Also strongly emphasizes the sense of responsibility within every believer. This is because in the Holy Quran also states that every human being should be responsible for what they had done. Therefore the purpose of this study was to investigate the differences students' personal responsibility in Kolej Universiti Islam Melaka. The study using research tool namely the Student Personal Responsibility Scale-10 which has been translated into Malay. The study was conducted at University College Islam Melaka and involving of 50 male and 50 female. The study using two methods of analysis descriptive in view of the demographic distribution of survey respondents. Inferential analysis method was used to examine the differences in students' personal responsibility by demographic factors. Data were analysis using the Statistical Package for Social Sciences (SPSS). The results of this study indicate that students' personal responsibility does not differ by sex. However, the study found that personal responsibility is different students according to their age and semesters. 125-132